Business or Security? Goals and Decision-Making Inside the French Oil Policy of the 1920s - I. E. Magadeev (Vestnik MGIMO-Universiteta)
The article aims to explore the interplay between economic and strategic reasons, which influenced the oil policy of the French government and business in the 1920s. The author demonstrates the heterogeneity and complexity of this policy the diverse nature of motives and interests behind the different attempts to acquire access to the oil. The French case throws some new light on the role of the “oil factor” in international relations and Great Powers’ politics. The article comprehensively deals with the topics often divided between different fields strategic studies, international political economy, diplomatic history. The author uses French archives to place Paris’ oil policy into the broader context of the French strategy and diplomacy in the first decade after WWI. Additional documents from the British and Russian archives help understand essential aspects of the Anglo-French and FrancoSoviet interactions around the “oil question.” After underlying the new strategic importance of oil, which became evident during WWI, and describing the oil dependence of France from the Anglo-American trusts (“Standard Oil” and “Royal Dutch-Shell”), the author traces the three key aims of the French oil policy. First, to diversify the supplies; second, to acquire control or direct access to the oil sources; and, finally, to consolidate the French business interests with the mediation of the state authorities. French actions in these three directions were interlinked, and they mirrored a specific situation of power and weakness of France after WWI. The article concludes that the strategic and economic reasons were interwoven inside the French oil policy. Though the French authorities perceived the growing strategic importance of oil sharply, they were not prepared to follow the clear étatist economic policy and did not try to make a radical change of the established rules of oil policy both inside the Third Republic and in the relations with “Standard Oil” and “Royal Dutch-Shell.”